Evolving Experimental Platforms to Evaluate Ulcerative Colitis. Issue 10 (22nd July 2022) - Sharma, Tiffany T.; Rabizadeh, Rebecca R.; Prabhakar, Vibhav S.; Bury, Matthew I.; Sharma, Arun K.
Abstract: Ulcerative colitis (UC) is a multifactorial disease defined by chronic intestinal inflammation with idiopathic origins. It has a predilection to affect the mucosal lining of the large intestines and rectum. Management of UC depends upon numerous factors that include disease pathogenesis and severity that are maintained via medical or surgical means. Chronic inflammation that is left untreated or managed poorly from a clinical stance can result in intestinal ulceration accompanied by resulting physiological dysfunction. End‐stage UC is mediated by surgical intervention with the resection of diseased tissue. This can lead to numerous health‐related quality of life issues but is considered a curative approach. Regimens to treat UC are ever evolving and find their basis within various platforms to evaluate and treat UC. Numerous modeling systems have been examined to delineate potential mechanisms of action. However, UC is a heterogenous disease spanning unknown genetic origins coupled with environmental factors that can influence disease outcomes and related treatment procedures. Unfortunately, there is no one‐size‐fits‐all model to fully assess all facets of UC. Within the context of this review article, the utility of various approaches that have been employed to gain insight into different aspects of UC will be investigated. Abstract : Approaches to mitigate inflammation observed in ulcerative colitis (UC) have been met with numerous technological challenges. Severe UC predisposes poor clinical outcome and lowered health‐related quality of life. The timely delivery of biocompatible anti‐inflammatory nanofibers in the form of supramolecular peptide amphiphiles can positively modulate protracted tissue inflammation in UC due to its innate molecular packing and saturating abilities.